Development of a person-centered interdisciplinary plan-of-care program for dialysis. Issue 8 (21st February 2020) - Dorough, Adeline; Forfang, Derek; Murphy, Shannon L; Mold, James W; Kshirsagar, Abhijit V; DeWalt, Darren A; Flythe, Jennifer E
Abstract: Background: Dialysis care often focuses on outcomes that are of lesser importance to patients than to clinicians. There is growing international interest in individualizing care based on patient priorities, but evidence-based approaches are lacking. The objective of this study was to develop a person-centered dialysis care planning program. To achieve this objective we performed qualitative interviews, responsively developed a novel care planning program and then assessed program content and burden. Methods: We conducted 25 concept elicitation interviews with US hemodialysis patients, care partners and care providers, using thematic analysis to analyze transcripts. Interview findings and interdisciplinary stakeholder panel input informed the development of a new care planning program, My Dialysis Plan. We then conducted 19 cognitive debriefing interviews with patients, care partners and care providers to assess the program's content and face validities, comprehensibility and burden. Results: We identified five themes in concept elicitation interviews: feeling boxed in by the system, navigating dual lives, acknowledging an evolving identity, respecting the individual as a whole person and increasing individualization to enhance care. We then developed a person-centered care planning program and supporting materials that underwent 32 stakeholder-informed iterations. Data from subsequent cognitive interviews led to program revisions intended to improve contextualization and understanding, decrease burden and facilitate implementation. Conclusions: My Dialysis Plan is a content-valid, person-centered dialysis care planning program that aims to promote care individualization. Investigation of the program's capacity to improve patient experiences and outcomes is needed.